2003
DOI: 10.1093/annonc/mdg300
|View full text |Cite
|
Sign up to set email alerts
|

Occult central nervous system involvement in patients with metastatic breast cancer: prevalence, predictive factors and impact on overall survival

Abstract: Patients with CNS involvement, whether occult or symptomatic, have an impaired survival. Occult CNS metastasis is relatively common, but impact on survival of treating occult CNS disease in patients with progressive systemic metastases is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
132
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(150 citation statements)
references
References 19 publications
11
132
2
5
Order By: Relevance
“…27 In the current series, only one patient who received antibody therapy was included. In this case, no change of expression was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In the current series, only one patient who received antibody therapy was included. In this case, no change of expression was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, the phenotype present in the intracerebral metastasis is already manifested in the primary tumour. Whether tumour patients with a risk profile for brain metastases should receive special surveillance to detect early and occult brain metastases 27 will have to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated increased risk of brain relapse in breast cancer patients with overexpressed or amplified HER2-neu gene [5][6][7][8]. HER2 abnormalities occur in 20-30% of invasive breast cancers and are associated with more aggressive tumor growth, increased risk of relapse and shorter survival [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…12 This was unusual because CNS screening is not commonly conducted on asymptomatic patients. However, nearly 15% of the women screened had occult brain metastases, and Her-2 overexpression by the primary tumor was predictive of occult brain metastases.…”
Section: The Emerging Her-2 Connectionmentioning
confidence: 99%
“…Survival among patients with occult brain metastases was shorter than that of patients without CNS disease but was similar to the survival of patients with symptomatic brain metastases. 12 The causes of these trends are unknown. One theory suggests that Her-2 overexpression endows tumor cells with increased metastatic aggressiveness to sites such as the lungs and may similarly augment metastatic propensity to the CNS.…”
Section: The Emerging Her-2 Connectionmentioning
confidence: 99%